On One Criterion for the Holomorphy of an Arbitrary Mapping of a Plane Domain into a Plane - Brodovich, M. T. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We prove the holomorphy of a function that, at every point, preserves either angles or dilations with respect to a certain set.